Effect of Ph and Leaf Extract Concentration of Pittosporum Undulatum on Gold Nanoparticles Synthesis - Castillo-Nara, A; Cottet-Bustamante, L; Bezares-Badilla, B (American Scientific Publishers, 2018)
In this work a methodology to produce high quality gold nanoparticles (AuNPs) from an aqueous extract of Pittosporum undulatum leaves, as reducing and capping agent, is presented. The gold nanoparticles obtained were characterized by UV-Vis, FTIR spectroscopy and purpleAu NPs synthesis produced a color change of the reaction mixture from light yellow Americanto dark Scientific and the absorption spectrum presented a maximal peak at about 530 nm, corresponding to surface resonanceplasmon (SPR) band, typical of the AuNPs formation. The effect of pH on AuNPs biosynthesis was determined and TEM analysis revealed that at pH 12 the AuNPs obtained presented mostly spheroidal geometry and a size range from 3 to 10 nm, with an average size of 6.3 nm in diameter. Through X-ray diffraction studies a crystallite size of 6.08 nm was obtained, indicating that nature of AuNPs was essentially monocrystalline. Finally, FTIR spectroscopy analysis revealed that compounds such as alcohols, terpenes, and sterols present in the leaves extract could be involved on the reduction of Au+3 and subsequent stabilization of nanoparticles. Therefore, using this methodology, it will be possible to obtain gold nanoparticles of small size and uniform geometry, which could be used in specific medical applications. © 2018, American Scientific Publishers. All rights reserved.